Kerukunan Bersama Pemerintah Desa Sri Tanjung, FKUB, Dan Tokoh Masyarakat Kerukuna - Ronald Sianipar; Mangiring Tua Togatorop; Erwin B. Joya; Adis Klara Yunita; Messy Causa Primay; Fredy Simanjuntak; Alfons R. Tampenawas (Sekolah Tinggi Teologi Real Batam, 2020)
This study aims to find out how the Religious Harmony Forum, the Sri Tanjung Village Head and community leaders in the Anambas Islands Regency carry out their roles as stipulated in the Joint Regulation of the Minister of Home Affairs and the Minister of Religion No. 9 and No. 8 of 2006. Research This is a qualitative research using descriptive analysis. The success of harmony and tolerance is largely determined by the role of the Government, Religious Harmony Forum (FKUB) administrators and community leaders as a management team that transmits policy information after it has been formulated at the Central level to the District. This structured accountability is based on the level of bureaucratic compliance with the bureaucracy above it or the level of the bureaucracy as formulated, the existence of a smooth routine and the absence of problems; and implementation and desired impact (benefits) of all existing and targeted programs. So that the policy implementation process as an effort to provide information or messages from higher institutions to lower institutions is measured for its performance success. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana Forum Kerukunan Umat Beragama, Kepala Desa sri tanjung dan tokoh masyarakat di Kabuapaten Kepulauan Anambas dalam melaksanakan perannya sebagaimana dengan fungsinya yang ditetapkan dalam Peraturan Bersama Menteri Dalam Negeri dan Menteri Agama No.9 dan No.8 Tahun 2006. Penelitian ini merupakan penelitian kualitatif menggunakan analisis deskriftif. keberhasilan sebuah kerukunan dan tolerasnsi sangat ditentukan oleh peran Pemerintah, pengurus FKUB dan Tokoh Masyarakat sebagai tim manajemen yang meneruskan informasi-informasi kebijakan setelah dirumuskan ditingkat Pusat sampai ke Kabupaten. Pertanggungjawaban terstruktur ini didasarkan pada tingkat kepatuhan birokrasi terhadap birokrasi di atasnya atau tingkatan birokrasi sebagaimana telah dirumuskan, adanya kelancaran rutinitas dan tidak adanya masalah; serta pelaksanaan dan dampak (manfaat) dikehendaki dari semua program yang ada dan terarah. Sehingga proses implementasi kebijakan sebagai upaya pemberian informasi atau pesan dari institusi yang lebih tinggi ke institusi yang lebih rendah diukur keberhasilan kinerjanya.